Neuroendocrine neoplasms of gastrointestinal tract and secondary primary synchronous tumors: A systematic review of case reports. Casualty or causality? (2019)
Neuroendocrine neoplasms (NENs) can arise in most of the epithelial organs of the body and are not a rare condition in the gastrointestinal tract (GIT). The presence of NENs in GIT associated with other secondary primary malignancies (SPM) has been considered an exotic event. This study aims to describe the case reports of NENs accompanied by synchronous primary tumors.